Predicting Organizational Citizenship Behavior Through Culture, Personality, and Transformational Leadership - Yosef Irianto Segu; Isman Kadar; Rita Retnowati (Cita konsultindo, 2026)
This study examines Organizational Citizenship Behavior (OCB) as a key determinant of organizational effectiveness within the Mardi Yuana Foundation, which operates under competitive pressures and resource constraints. OCB has gained increasing importance in modern organizational transformation, as highlighted by Deloitte (2023), reporting a 23% productivity increase in highly engaged organizations, and Kim and Park (2022), emphasizing OCB’s role in resilience and innovation. This research aims to analyze both direct and indirect effects of mutual cooperation, organizational culture, personality, and transformational leadership on OCB, as well as to identify priority improvement areas using the SITOREM approach. A quantitative survey method was employed involving 138 respondents selected through proportional random sampling. Data were analyzed using Path Analysis and SITOREM. The findings reveal that mutual cooperation has a significant positive direct effect on OCB (β=0.603), while organizational culture, personality, and transformational leadership do not have significant direct effects. However, all variables demonstrate significant indirect effects through transformational leadership as a mediating variable. This study contributes by providing an integrative, evidence-based model and actionable insights for enhancing OCB strategically.